4 FIELD REGIMENT IN EAST AFRICA, 1939-1941 - Jacobs, F.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
"Those were happy care-free, though at times, worrying, days, during which we were ill-equipped - the home front was ill organised - and fortunately had to fight only a half-hearted enemy." - Lt Col M. D. Mackenzie